P548 Vedolizumab clinical decision support tool predicts hospitalisation, surgery, and healthcare resource utilisation. (25th January 2019) - Dulai, P S; Huang, Z; Wan, Y; Luo, M
Abstract: Background: A clinical decision support tool (CDST) has been developed and validated to predict clinical and endoscopic remission with vedolizumab (VDZ) in Crohn's disease (CD). 1 We assessed whether this CDST could be applied in real-world settings using retrospective claims database to predict differences in CD-related hospitalisation, surgery, and other healthcare resource utilisation. Methods: The Truven MarketScan Database was used to identify CD patients treated with VDZ after 1 May 2014. Patients were stratified into low or high probability of VDZ response based on the previously validated CDST. Rates of CD-related hospitalisation and surgery, rates of other healthcare resource utilisation, and related costs (hospitalisation, surgery, emergency department (ED) visit, office visit, endoscopy, imaging, and laboratory tests) were compared between the low and high probability of VDZ response groups for the 12 months after VDZ initiation. Results: A total of 1445 CD patients ( n = 935 high probability, n = 510 low probability) were included (mean age, 43.4 years; 57.2% female). A significantly lower proportion of the high-probability group experienced a CD-related hospitalisation (14.4% vs. 19.6%, p = 0.011) or CD-related surgery (13.5% vs. 23.3%, p < 0.001) during the 12 months after VDZ initiation. The high-probability group had significantly lower non-drug-related healthcare expenditure costs during the 12 months after VDZ initiation (mean 8842 vs. 14591, p < 0.001), which was driven by the lower costs incurred for CD-related hospitalisation and surgery. No significant difference was observed between the low- and high-probability groups for rate of ED visits, endoscopy, imaging, or laboratory tests. Conclusions: The VDZ CD CDST can stratify probability of CD-related hospitalisation and surgery, and we observed a significant difference in non-drug–related healthcare cost between the high and low probability of VDZ response groups. Further studies are needed to assess whether up-front stratification of CD patients with this tool could optimise the cost-effectiveness of VDZ utilisation. Reference 1. Dulai PS, Boland BS, Singh S, et al. Development and validation of a scoring system to predict outcomes of vedolizumab treatment in patients with Crohn's disease. Gastroenterology. 2018 Sep;155(3):687-695.e10.